PENGARUH MODEL PEMBELAJARAN STAD TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 1 SOMAMBAWA - Theresia Venty Fau, Yohanna; Solomasi Hulu, Liberkat; Rianghati Luaha, Lusia (Universitas Cokroaminoto Palopo, 2025)
The type of research used is quantitative with a quasi-experimental approach. The results of the study based on the prerequisite test that the data is normally distributed for the normality test and both classes are said to be homogeneous. Based on the hypothesis test, it is known that the control class has a t-count value of 5.81345> t-table 1.71714 with a sig. (2-tailed) value with a two-tailed test of 0.023 <0.05. The experimental class has a t-count value of 5.67976> t-table 1.70814 with a two-tailed test of 0.032 <0.05. Based on these data, it is concluded that there is an influence of the Student Teams Achievement Division learning model on the learning outcomes of class XI students of SMA Negeri 1 Somambawa. The researcher's suggestion is that biology teachers are expected to use the Student Teams Achievement Division learning model in learning because this learning model can provide opportunities for students to be actively involved in learning.